Methodological and aerobic capacity adaptations of high‐intensity interval training at different altitudes in distance runners: A comprehensive meta‐analysis - Sisay Fentaw; Tefera Tadesse; Zerihun Birhanu (Physiological Reports)
Abstract High‐intensity interval training (HIIT) in hypoxia has demonstrated superior increases in aerobic capacity (VO2 max) adaptations, but this has not been explored in distance runners. This study examined the methodological and VO2 max adaptations of HIIT under different altitude conditions in distance runners. We searched the PubMed, ProQuest, Europe PMC, ScienceDirect, and Cochrane databases until August 2024. Among the 1183 reviewed studies, six studies were included. The PEDro score determined the methodological quality, and a meta‐analysis was performed using Jamovi software. The results revealed that VO2 max improved more in hypoxic (4.4%–13%) HIIT than in normoxic (1%–8.3%) HIIT. The meta‐analysis results revealed that the effect of HIIT under hypoxia on the VO2 max overall standardized mean difference (SMD) was 0.68, with a 95% confidence interval [0.3, 1.06], p < 0.001. Conversely, the pooled SMD was not related to the type of hypoxia (p = 0.4), training status (p = 0.36), intervention week (p = 0.82), and sex (p = 0.32). In conclusion, HIIT under hypoxia achieves a greater VO2 max improvement than normoxia. Endurance athletes and coaches could plan to benefit from such training. However, studies on females using different HIIT protocols and participants at different natural altitudes are limited. This review is registered under the PROSPERO CRD42024578473.